Investigating year 8 student perceptions of using science subject specific assessment without level criteria. A new era in developing autonomous behaviours in science learning? - Fenton, Beth (2016)
The focus of this research is to find out how year 8 pupils at my school feel about being assessed in their learning without the use of levels. More specifically, if they perceive it motivates them to learn more. Such a study is important as the Department for Education have removed assessment levels at key stage three therefore allowing each school to develop their own assessment framework and progress reporting structures. I would like to see how our students perceive the replacement assessment framework my school introduces and if they think that it makes them more motivated to learn. I will use the findings of this study to develop and improve the framework and how it is implemented further. The research approach adopted in this dissertation is the use of the Intrinsic Motivation Inventory (Deci and Ryan, 2016), in conjunction with a focus group interview. The findings from this research indicated that the introduction of the new assessment framework increased pupil perception of their motivation to learn. Additionally, pupils found the new framework complicated to understand and indicated a preference for levels. This dissertation recommends that written feedback should not emphasise the pupil’s current attainment, but focus on how to improve. Additionally to promote a better engagement with the assessment criteria there should be more opportunity for self-assessment.